STUDI PENGEMBANGAN TERAPI MUSIK ISLAMI SEBAGAI RELAKSASI UNTUK LANSIA (Jurnal Bimbingan dan Konseling Islam, 2013)
In this study, researchers developed and tested a product of Islamic music therapy as a relaxation for the elderly in the Elderly IHC Kurnia Jemurwonosari Surabaya. The purpose of this study was to test the feasibility and to produce Islamic music therapy as a relaxation for the elderly. Researchers used a research method development (R&D) to develop and get good results and maximum, with the kind of qualitative and quantitative research. Results of research and field trials found that the process of Islamic music therapy as a relaxation for the elderly in the Elderly Kurnia IHC performed in 3 stages, namely 1) Supervising music therapy provides early explanation of the usefulness of music therapy and also for the elderly, 2) the process of music therapy the elderly played music used music as therapy for 5 minutes, 3) Discussion and evaluation. The final results in the calculation of the questionnaire participants Islamic music therapy as a relaxation for the elderly amounted to 80.94 % (very effective). And Islamic music therapy product designed to meet the standard test is appropriate categories with the final result 83.33 %.Keywords : Islamic Music Therapy , Relaxation , Elderly .